2016
DOI: 10.1097/fjc.0000000000000364
|View full text |Cite
|
Sign up to set email alerts
|

CTRP9 Ameliorates Pulmonary Arterial Hypertension Through Attenuating Inflammation and Improving Endothelial Cell Survival and Function

Abstract: Endothelial dysfunction and inflammation are believed to be 2 primary instigators of pulmonary arterial hypertension (PH). C1q/TNF-related protein 9 (CTRP9) plays important roles in anti-inflammation and improvement of epithelial function. However, the role of CTRP9 in the progression of PH remains still unclear. In this study, the role and mechanism of CTRP9 in the PH progression were explored. First, serum CTRP9 contents and CTRP9 mRNA expression in the pulmonary artery epithelial cells from patients with PH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 29 publications
4
27
0
Order By: Relevance
“…cTRP4 was demonstrated to protect against apoptosis induced by chemotherapeutics and thereby promote tumor cell survival (3). The present study was the first to report the anti-apoptotic effect of C1QTNF6 in GC AGS cells; the results are consistent with those of previous studies (28)(29)(30), which suggested that c1QTNF family proteins primarily perform cytoprotective and anti-apoptotic functions. In addition, the results of the present study may be applied to a C1QTNF6-knockout animal model to extend and confirm the results derived from a cell culture model.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…cTRP4 was demonstrated to protect against apoptosis induced by chemotherapeutics and thereby promote tumor cell survival (3). The present study was the first to report the anti-apoptotic effect of C1QTNF6 in GC AGS cells; the results are consistent with those of previous studies (28)(29)(30), which suggested that c1QTNF family proteins primarily perform cytoprotective and anti-apoptotic functions. In addition, the results of the present study may be applied to a C1QTNF6-knockout animal model to extend and confirm the results derived from a cell culture model.…”
Section: Discussionsupporting
confidence: 92%
“…A number of protein members are involved in the regulation of cell apoptosis. Administration of cTRP9 was demonstrated to attenuate cardiomyocyte apoptosis following acute myocardial infarction (26) or myocardial ischemia reperfusion (27), and to decrease the apoptotic rate of primary pulmonary artery epithelial cells due to pulmonary arterial hypertension (28). cTRP3 protected bone marrow derived mesenchymal stem cells from hypoxia-induced apoptosis through the phosphoinositide 3-kinase/protein kinase B signaling pathway (29).…”
Section: Discussionmentioning
confidence: 99%
“…Administration of CTRP9 attenuated cardiomyocyte apoptosis and myocardial remodeling in mice after acute myocardial infarction [25]. CTRP9 attenuates the apoptosis of primary pulmonary artery epithelial cells, which is essential for amelioration of pulmonary arterial hypertension [26]. In the presence of CTRP9, the cardiac infarction, and cardiomyocytes apoptosis are markedly reversed in myocardial ischemia reperfusion rats [27].…”
Section: Discussionmentioning
confidence: 99%
“…It shows that CTRP9 plays an important role in protection of epithelial function which can be embodied by eNOS, endothelin (ET) ‐1 and matrix metalloproteinase (MMP) ‐2 (Li, Geng, Wang, Cheng, & Xu, ). Interestingly, serum CTRP9 concentrations and CTRP9 mRNA expression levels both deceased in PH patients compared with the normal participants (Li et al, ).…”
Section: Introductionmentioning
confidence: 99%